Community participation in the management of land conservation areas and educational tourism at forest farmer groups, Panderman District Batu, Batu City, Indonesia - Yayuk Yuliati; Bekti Nur Utami (Caspian Journal of Environmental Sciences)
The COVID-19 pandemic has significantly impacted the development of agroforestry tourism areas in Batu City, Indonesia. An area becomes resilient and robust through community participation in adapting, especially in the forestry village environment. This study will reveal community participation in managing land conservation areas and educational tourism in Oro-Oro Ombo Village, Batu City. The study is a qualitative research type of centralized interview to find community participation when managing a land conservation area. In February 2022, there were 25 informants in the form of 20 members of forest farmer groups, 6 village institutions, and 4 related official institutions who were interviewed using the in-depth interview method. The interview results were collected and processed using the help of a qualitative application, i.e., Altas.ti version 9. The dissemination of interview text was propagated using an enumerator with a voice recorder help tool. The results showed that the results of data processing of the word 'Management' are the words with the most frequency, i.e., 7.43% of all research data sources community. Participation in the management of land conservation areas and educational tourism, followed by the words 'area' and 'conservation', was 6.86% of all research data sources. If concluded with four stages of participation, i.e., planning, implementing, utilizing results and evaluating the community, they were very concerned about the sustainability of conservation land management, so that they have full participation in advancing this land as a potential economic land. This example can be used as a government policy to find the best method to foster community awareness to produce excellent participation in advancing a forestry area. The advanced Forest Farmers Group will become a new face in empowering the community in the future.